(untitled) (Journal of the College of Basic Education, 2022)
The research aimed to identify the use of physics teachers of the realistic teaching , their cognitive orientations and the correlation between use of physics teachers of the realistic teaching , their cognitive orientations. The research community consisted of all physics teachers in Al-Diwaniyah Governorate, who numbered 184, and they represented this research sample. The researcher prepared two tools, the first to identify the teachers’ use of realistic teaching, consisting of three domains (learning content analysis, planning, teaching implementation) each field, including 11 items, while the second tool was the cognitive orientation scale , it consisted of four domains: (the tendency to know that knowledge is fixed, belief in simple knowledge, belief in rapid learning, belief in confirmed knowledge) , the scale consists of (42) items, each item had five alternatives: (agree, often, sometimes, rarely, not agree), , the researcher used a number of statistical instruments to calculate the results that confirmed the teachers’ use of realistic teaching and their positive attitudes towards knowledge and the existence of a strong positive correlation between using of physics teachers of realistic teaching and their cognitive orientations. In light of the research results, the researcher put a number of conclusions and made a number of recommendations and suggestions.